2022
DOI: 10.14740/jh1054
|View full text |Cite
|
Sign up to set email alerts
|

Oral Chemotherapy Application in Elderly Patients With Diffuse Large B-Cell Lymphoma: An Alternative Regimen in Retrospective Analysis

Abstract: Background A combination of rituximab, cyclophosphamide, doxorubicin, vincristine, and prednisone (R-CHOP) is considered the standard treatment for diffuse large B-cell lymphoma (DLBCL). However, no standard treatment has been established for older patients (age ≥ 75 years). This study retrospectively analyzed different treatment strategies in older patients with DLBCL with different chemotherapy regimens and compared the survival rate of patients using oral or intravenous form cyclophosphamide an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…There may thus be selection bias regarding the ineligibility for standard-dose chemotherapy because no proper randomization could be achieved. R-CHOP is not standardized for older patients with DLBCL, particularly for those aged ≥80 years [ 17 , 18 ].…”
Section: Considerations In the Older Populationmentioning
confidence: 99%
See 2 more Smart Citations
“…There may thus be selection bias regarding the ineligibility for standard-dose chemotherapy because no proper randomization could be achieved. R-CHOP is not standardized for older patients with DLBCL, particularly for those aged ≥80 years [ 17 , 18 ].…”
Section: Considerations In the Older Populationmentioning
confidence: 99%
“…Peyrade et al evaluated and recommended R-mini-CHOP as standard therapy in patients aged >80 years with DLBCL [ 28 ]. Liao et al retrospectively compared R-CHOP, R-mini-CHOP, and R-CVOP in patients aged ≥75 years and concluded that OS was comparable and differences in PFS were insignificant [ 18 ]. Verner et al undertook a phase 2 study of R-mini-CHOP plus ibrutinib in patients aged >75 years and showed that, although 2-year OS was 68%, ibrutinib was discontinued in 25% of patients, primarily because of adverse events [ 41 ].…”
Section: Reduced-intensity Chemotherapymentioning
confidence: 99%
See 1 more Smart Citation